A Route 66 companion - Dunaway, David King; Waldmire, Robert (University of Texas Press, 2012)
"Even before there was a road, there was a route. Buffalo trails, Indian paths, the old Santa Fe trace--all led across the Great Plains and the western mountains to the golden oasis of California. America's insatiable westering urge culminated in Route 66, the highway that ran from Chicago to Los Angeles. Opened in 1926, Route 66 became the quintessential American road. It offered the chance for freedom and a better life, whether you were down-and-out Okies fleeing the Dust Bowl in the 1930s or cool guys cruising in a Corvette in the 1960s. Even though the interstates long ago turned Route 66 into a bylane, it still draws travelers from around the world who long to experience the freedom of the open road. A Route 66 Companion gathers fiction, poetry, memoir, and oral history to present a literary historical portrait of America's most storied highway. From accounts of pioneering trips across the western plains to a sci-fi fantasy of traveling Route 66 in a rocket, here are stories that explore the mystique of the open road, told by master storytellers ranging from Washington Irving to Raymond Chandler, Joan Didion, Sylvia Plath, Leslie Marmon Silko, and John Steinbeck. Interspersed among them are reminiscences that, for the first time, honor the varied cultures--Native American, Mexican American, and African American, as well as Anglo--whose experiences run through the Route 66 story like the stripe down the highway. So put the top down, set the cruise control, and "make that California trip" with A Route 66 Companion."--Page 4 of cover.